Comparison between isotope ratio mass spectrometry (IRMS) and cavity ring-down spectroscopy (CRDS) for analysing the carbon isotope ratio and detection of adulteration in coconut water - Sang Arun Meepho (2022)
This study investigated the carbon isotope ratio (¹³C/¹²C, δ13C in unit of parts per thousand or per mill, ‰) of different coconut water samples using elemental analysis isotope ratio mass spectrometry (EA-IRMS) and combustion module cavity ring-down spectroscopy (CM-CRDS). Natural coconut water from young coconuts from 12 provinces in Thailand (n = 94), adulterated coconut water containing three sweeteners (sucrose, glucose and fructose) at different concentrations and eight brands of commercial coconut water were analysed. The δ13C of all samples were not significantly different (P > 0.05) between the EA-IRMS and CM-CRDS analyses. The natural coconut water (C3 plant) had δ13C ranging from −21.58‰ to −27.79‰ (mean −24.64 ± 0.91‰). Three sweeteners (C4 plant) contained δ13C between −11.46‰ to −13.16‰. The use of δ13C determination can detect adulteration of a singular extraneous sweetener (either glucose or sucrose) down to a level of 2% of adulteration. For the detected δ13C values of commercial products labelled as ‘no added sugar’, about 50% of products were adulterated. This study demonstrates that CM-CRDS can be used as an alternative analytical platform to EA-IRMS for detecting adulterated products, especially coconut water.